Levels of Representation of the Computing Process and Workload on LAN - O. M. Demidenko (Цифровая трансформация)
The article considers the computational process in local area network at four levels of interaction referring to their possible decomposition into parts and the connection between these parts. Classification of types of workload is presented. A solution to the problem of the rigid dependence of the research results on the features of the architecture of the applied equipment is proposed.